Keanekaragaman Jenis Mamalia di Hutan Kota Ranggawulung, Subang, Jawa Barat - Muhammad Muhajir Hasibuan; Siti Rabiatul Fajri; Sucika Armiani; Rizki Kurnia Tohir; Shinta Nur Rahmasari (Jurnal Penelitian Pendidikan IPA, 2022)
Ranggawulung urban forest is one of the remaining vegetated sites in Subang. That place needs to be managed sustainably because of its potential to be a strategic location for biodiversity. Biodiversity studies in Rangawulung urban forest need to be conducted periodically to assess and control the impact of urban development. This study was undertaken to evaluate biodiversity in Subang City, especially Ranggawulung Urban Forest as an indicator of biological management in urban areas. There were ten species of mammals found in the Ranggawulung City Forest area from six families. One of the species found, the Javanese slow loris (Nycticebus javanicus), is a protected animal in Minister of Environment and Forestry regulations (PermenLHK Number P.106/2018). The animal is categorized as CITES Appendix I and Critical according to the IUCN red list. Diversity (H'), richness (Dmg), and evenness (E') indices of the area species were 2.03, 2.06, and 0.92, respectively. Ranggawulung Urban Forest is considered important as an animal habitat in Subang City and needs to be managed properly and sustainably.